Analysis of the survival rate of cholera vibrions of various serogroups at low water temperature in surface reservoirs and optimization of monitoring studies for cholera in the subjects of the Russian Federation - Kazmina, V. S.; Gayevskaya, N. E.; Kruglikov, V. D.; Menshikova, E. A.; Duvanova, O. V.; Ezhova, M. I.; Shipko, E. S.; Evteev, A. V.; Podoynitsina, O. A.; Selyanskaya, N. A.; Yeghiazaryan, L. A.; Bodraya, P. V. (Medicinskij vestnik Ûga Rossii, 2025)
Objective: to analyse the possibility of Vibrio cholerae survival in surface reservoirs of the Russian Federation subjects under conditions of low water temperature, compared to the temperature optimum for the growth and reproduction of these microorganisms in environmental objects (EO). Materials and methods: oﬃcial data of the reference centre for cholera monitoring on the detection of Vibrio cholerae strains in the aquatic environmental objects of the Russian Federation subjects within the framework of monitoring studies for the period from 2019 to 2024 were used. Monitoring studies were organised and conducted in accordance with the current regulatory and methodological documentation. All isolated Vibrio cholerae strains were identiﬁed by regulated bacteriological, serological, molecular-biological methods. Results : 553 strains of Vibrio cholerae O1 serogroup (three of them toxigenic) and 13013 strains of NAG-vibrios were isolated for the period from 2019 to 2024. The range of minimum water temperatures of surface reservoirs from which the ﬁrst strains of Vibrio cholerae were isolated in the administrative territories of types I–III on cholera epidemic manifestations was in the range from 1 °C to 15 °C, which is lower than the temperature optimum (above +16 °C) for their growth, and indicates the possibility of survival of these microorganisms in conditions of low temperatures of water bodies, and, therefore, does not exclude the possibility of spreading infection by water in the event of a toxigenic strain entering the reservoir. Conclusions: detection of NAG vibrios and non-toxigenic strains of Vibrio cholerae O1 serogroup in the water of surface reservoirs at temperatures up to 15 °C is an indicative sign of the existence of conditions conducive to the spread of infection in case of cholera importation into the territory of the Russian Federation and indicates the expediency of an earlier start and a later end of cholera monitoring studies in Russia.